Heritage in Augmented Reality - Ramadhan, Seno Surya; Ganendra, Firzatullah Danevan; Brilian, Ramdlan Siraj Rio; Yahya, Saiful (LPPM STIKI Malang, 2024)
This research explores the application of augmented reality (AR) technology to promote the historical heritage of colonial architecture in East Java, with a focus on Malang. By creating immersive 3D visualizations of iconic buildings, the project aims to document and preserve cultural heritage, raise public awareness, and support sustainable urban planning. The project aligns with Sustainable Development Goals (SDGs) 4 and 11, fostering quality education and sustainable cities.